The Effect of Time Budget Pressure, Locus of Control and Work Stress on Auditor's Dysfunctional Behavior With Machiavellian Characteristics As A Moderating Variable - Nazihah, Yasmin; Taufan, Januar (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this study is to examine he influence of time budget pressure, locus of control, and job stress on dysfunctional auditor behavior, with Machiavellian traits as a moderating variable. The research is motivated by the increasing number of audit irregularities that have impacted the decline in audit quality. The study was conducted on auditors working at Public Accounting Firms in the South Jakarta area. The method used is a quantitative approach with data collection through questionnaires, and data analysis using Structural Equation Modeling with the SmartPLS version 4.1 application. The results show that time budget pressure and Machiavellian traits have a positive and significant effect on dysfunctional auditor behavior, while locus of control has a significant negative effect. Job stress does not have a significant effect. In the moderation test, only Machiavellian characteristics were proven to significantly and negatively moderate the relationship between locus of control and dysfunctional behavior, while other moderation relationships were not significant. These findings highlight the importance of managing work pressure and understanding individual auditor characteristics to prevent dysfunctional behavior and maintain audit quality.